Left Shifting of Language Related Activity Induced by Bihemispheric tDCS in Postacute Aphasia Following Stroke - Feil, Sarah; Eisenhut, Peter; Strakeljahn, Frauke; Müller, Sarah; Nauer, Claude; Bansi, Jens; Weber, Stefan; Liebs, Alexandra; Lefaucheur, Jean-Pascal; Kesselring, Jürg; Gonzenbach, Roman; Mylius, Veit (Frontiers in Neuroscience, 2019)
Both anodal transcranial direct current stimulation (tDCS) of the left IFG and cathodal stimulation of the right IFG were shown to improve rehabilitation of stroke patients with Broca´s aphasia. The study aimed at assessing the impact of a bihemispheric IFG stimulation compared to sham on postacute non-fluent aphasia. Twelve patients with non-fluent aphasia were included at least 4 weeks following cerebral stroke. Ten daily sessions of 2mA bihemispheric verum or sham tDCS (anode on left IFG and cathode on right IFG) were performed concomitantly with individual language therapy in a double-blinded randomised controlled study with parallel group design. Language functions (i.e. communication (ANELT), picture naming and the Aachener Aphasia testing (AAT)) were assessed up to one month following tDCS. The picture naming task significantly improved (increased number of nouns) at the end of the tDCS procedure in the verum but not sham group. Improvements in the picture naming task and the communication task of the AAT at 4 weeks after tDCS procedure were only seen in the verum group. In patients with postacute cerebral stroke, repeated sessions of tDCS applied on both IFG concomitantly with language therapy were able to induce immediate effects on picture naming presumably due to an early left shift of language-associated function that maintained for 4 weeks. Effects on clinically relevant communicative abilities are likely.